Advanced Information Systems Engineering Workshops: CAiSE 2015 International Workshops, Stockholm, Sweden, June 8-9, 2015, Proceedings - Persson, Anne (Springer, 2015)
This book constitutes the thoroughly refereed proceedings of seven international workshops held in Stockholm, Sweden, in conjunction with the 27th International Conference on Advanced Information Systems Engineering, CAiSE 2015, in June 2015. The 38 full and nine short papers were carefully selected from 107 submissions.